An Antipodal Vivaldi Antenna Design for Torso Imaging in a Coupling Medium - Çayören, Mehmet; Bilgin, Egemen; Bilgin, Egemen; Joof, Sulayman; Doğu, Semih (IEEE, 2021)
An antipodal Vivaldi antenna designed to operate in a coupling medium with a relative dielectric constant of e r = 25 for microwave imaging of torso is presented in this paper. The proposed antenna is similar to the conventional antipodal Vivaldi antenna but with optimized parameters to radiate in the desired coupling medium. The antenna has a size of 120×70 mm2 and operating over 230-1000 MHz frequency bandwidth with a peak gain of 5.42 dBi and peak front-to-back ratio of 14.3 dB. The designed antenna shows a better performance compared to other antennas used for microwave torso imaging. To assess the actual performance, a realistic human torso phantom is implemented to detect the water accumulation in the lungs, and as the inversion method linear sampling method is used. The 3-D reconstruction results show that the proposed antenna can be a candidate for microwave torso imaging applications.
Keywords: Linear sampling method (lsm); Microwave imaging (mwi); Antipodal vivaldi antenna (ava)